Sperm Characteristics in Hypothyroid Male Albino Rats Treated With Vitex Agnus Castus Extract - Sumayah Faruq Kasim; Fouad Ziedan Hamzah (مجلة الانبار للعلوم البيطرية, 2023)
To evaluate the probable protective effect of vitex agnus castus extract on sperm characteristics in hypothyroid male albino rats. Forty adult male albino rats (200–250 g) were divided into 4 groups, 10 rats in each group. Negative control (First Group) got normal saline every day. After hypothyroidism, groups 2–4 received vitex agnus castus extract and/or levothyroxine (L-T4). (Second Group) received normal saline as a positive control, (Third Group) received vitex agnus castus extract (300 mg/kg body weight), and (Fourth Group) received L-T4 (0.1 mg/kg/day). HYPO (positive) increased TSH but decreased T3 and T4, while HYPO+ THYROXIN and HYPO+V.A.C decreased TSH and increased T3 and T4 compared to the HYPO (positive). THYROXIN and V.A.C decreased Malondialdehyde (MDA), but HYPO (positive) increased it. Catalase (CAT), Glutathione Peroxidase (GPX) and Superoxide dismutase (SOD) decreased in the HYPO (positive) group compared to the control treatment and increased in THYROXIN and V.A.C treatments compared to HYPO (positive) group. Indicators of sperm characteristics showed that the HYPO (positive) treatment caused a significant decrease in (sperm count, general motility, progressive motility, viability, and morphology) compared to the control, while both treatments of HYPO, whether with THYROXIN or V.A.C, increased all five indicators significantly despite the lack of difference between them and control in terms of impact. Vitex agnus castus' antioxidant characteristics make it a potential preventative measure against hypothyroidism's deleterious impact on sperm quality and antioxidant testicular levels